Análise das notificações de hemovigilância no sistema notivisa do hemocentro coordenador e das agências transfusionais de Teresina-PI no período de 2012 a 2015 - Chaves, Lucelia Regina de Castro (2016)
Blood transfusion is indispensable in the treatment of some patients, but not without risk. In addition to the possible transmission of infectious diseases by the blood, transfusion incidents of different degrees may occur. The notifications in the NOTIVISA system are important for the safety and quality of hemotherapy assistance. The objective of this study was to analyze the transfusion incidents in the Haemovigilance System at the Hemocentro Coordinator and in the transfusion agencies of Teresina, from January 2012 to July 2015. This is a retrospective epidemiological, observational and qualitative study. The data were obtained through the notifications made by the hemotherapy services (HC and AT's) in the NOTIVISA System and analyzed through the Microsoft Office Excel 2013 program, represented in charts and tables with a total of 181657 transfusions and 186 notifications in the four years of the analysis, with red cell concentrate being the most used, predominantly males with an age group above 40 years. The type of hemocomponent that presented the greatest number of reactions was the red cell concentrate with (84.95%), in relation to the time of onset of the reactions, the immediate ones were the ones with the highest incidence, totaling 98.38%, regarding the diagnosis the non-hemolytic febrile reaction was prevalent with (45.16%), and the most frequent clinical symptoms were fever, chills and urticaria. The study points to a high underreporting rate to the NOTIVISA system in the area of haemovigilance in the analyzed services, compared to that recommended by the current legislation and based on the scenario of the haemovigilance system of France where three transfusion reactions are estimated for each thousand transfusions, because of the number of transfused blood components, 544 RTs are estimated. It is hoped that this work will be able to subsidize both the health services that provide hemotherapy assistance and the professionals who work in this area, with the implementation and implementation of continuing education programs, hospital transfusion committees, to assist in hemotherapy, safety minimizing the risks inherent in the therapeutic use of blood and blood components by preventing and reducing them in order to improve transfusion quality and safety throughout the blood cycle from donor to recipient.